PENGARUH MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KREATIVITAS PESERTA DIDIK PADA PEMBELAJARAN SENI BUDAYA KELAS V SDN 06 KODO KOTA BIMA - Uswatun Hasanah; Mirham Nurul Hairunnis; Irmaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low creativity of students in Arts and Culture learning at SDN 06 Kodo, Bima City. Learning that is still centered on the teacher causes students to be given less opportunity to explore ideas and innovate in their work. The purpose of this study is to determine the effect of the application of the Discovery Learning learning model on increasing the creativity of fifth grade students in Arts and Culture subjects. The type of research used is a pre-experimental design with a One Group Pretest-Posttest Design. The research subjects were 14 fifth grade students. Data collection was carried out through practical tests and creativity tests covering aspects of refinement, flexibility, uniqueness, and idea development. Data were analyzed using normality tests, reliability tests, and hypothesis tests with the help of the SPSS version 26 program. The results showed an increase in the average student score from 75.00 in the pretest to 90.00 in the posttest. The peered sample t-test produced a significance value (Sig. 2-tailed) of 0.000 <0.05, which means there is a significant difference between the pretest and posttest results. Thus, it can be concluded that the implementation of the Discovery Learning model has a positive and significant impact on increasing student creativity in Arts and Culture learning in elementary